Desnutrición y anemia en preescolares que acuden al Centro de Salud número 3 de la ciudad de Loja - Chamba Pineda, Diego Osmany (2016)
The World Health Organization defines malnutrition as cellular imbalance between supply of nutrients and energy, and the body needs them to ensure growth, maintenance and specific organic bodily functions. Studies have been conducted between the association of anemia and malnutrition but in our environment there is none, so this research was considered the main objective was to evaluate the relationship between malnutrition and anemia in preschool children who attended the Health Center # 3 city of Loja, during 2015. The specific objectives were to identify malnourished preschoolers served in this House Health and establish the degree of malnutrition among themselves and identify patients with anemia assessing the degree of severity at the same. The study population was of 147 children who met the inclusion criteria required and according to the curves of growth and development implemented by the MSP could be part of this study. Concomitantly laboratory studies were reviewed and taken into consideration values for hemoglobin and hematocrit for the study. It was found that malnutrition affects a significant number of children in the mild degree of malnutrition with 40.1%, severe malnutrition affects only 12.2%. Female gender was the most affected with 62.6%. 71.2% have a degree of mild anemia and 2% has severe anemia. The most affected is the male gender with 51.6%. Regarding the association between malnutrition and anemia was found to be significant because 100% of malnourished children showed some degree of anemia. Keywords: malnutrition, anemia, preschool.